G219(P) Auditing Our Paediatric Assessment Unit Against National and Local Standards. (24th May 2017) - Styles, KF; Webster, A; Weerasinghe, O; Shah, D
Abstract : Aim: Does our Paediatric Assessment Unit (PAU) meet national and local standards? It is a 6-bedded unit, in a busy district general hospital, open 24 hours a day seeing primary care and A and E referrals. Methodology: Standards are taken from RCPCH Facing the Future 2015, RCPCH Paediatric Emergency Care standards and local policy. 50 sets of notes were audited, 10 per day, over 5 days (including a weekend day), spread out over 24 hours. The audit cycle was completed during November 2015, March 2016 and August 2016. After each cycle the results were presented locally. Results: Discussion: During the audit period the PAU has become progressively busier and systems have evolved. The unit is now 'paperless' using the 'System One' IT programme. Nurses report triage happens within 15 min but is documented later onto System One as writing on a tablet during triage affects communication. The Child Protection Register is now checked by both administration and nursing staff. There is increased junior medical staffing with daily Consultant presence 2 pm–10pm, including at handovers. The Consultant carries the 'Hotline Referral Phone' releasing the registrar for clinical care. Doctors believe more patients are seen within 1 hour compared with results, however time of clerking is often not documented. The fall in number of patients discussed with Consultant probably reflects increased experience of juniors over the year. It is not currently possible to review old records on System One to see time of Consultant review. Conclusions: Overall the unit is performing well against local and national standards but better documentation will demonstrate this. This requires ongoing System One training and development, plus triage training.